1983
DOI: 10.1302/0301-620x.65b2.6826616
|View full text |Cite
|
Sign up to set email alerts
|

Closed vertebral biopsy

Abstract: A study of cadaveric vertebral biopsy and a review of 100 clinical biopsies has shown that needles and trephines producing tissue specimens of two millimetres or more in diameter can be expected to give a high degree of diagnostic accuracy. The erythrocyte sedimentation rate was a more useful screening investigation than were estimations of serum alkaline phosphatase. The complications are described. It is suggested that patients with painful thoracic metastases and evidence of progressive cord compression sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 9 publications
0
41
0
1
Order By: Relevance
“…The posterolateral approach is normally used for obtaining biopsy under fluoroscopic or CT guidance in cases of thoracic or lumbar spine (19)(20)(21). However, the risk correlated with this process varies from 0 to 26% and is associated with various complications, including pneumothorax, hematoma, neurological lesions, root pain and infective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The posterolateral approach is normally used for obtaining biopsy under fluoroscopic or CT guidance in cases of thoracic or lumbar spine (19)(20)(21). However, the risk correlated with this process varies from 0 to 26% and is associated with various complications, including pneumothorax, hematoma, neurological lesions, root pain and infective disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001 Stirling [6][7][8][9] using serological tests demonstrated [10] that culture of intervertebral disc material from 36 patients operated upon for severe sciatica, showed that 53 % grew Propionebacterium acnes. In the knowledge that Modic changes-bone oedema are present in only 6 % of the general population [11], but are present in 35 % of a back pain population, and the knowledge that these changes may be due to infection, Albert et al [12] asked the question whether nuclear tissue so infected led to such changes.…”
Section: Back Painmentioning
confidence: 99%
“…They emphasise the importance of obtaining bacteriological confirmation by needle biopsy. Unfortunately since these investigations are now frequently carried out by Radiologists, and they use fine diameter needles, and achieve only 70 % positive culture, rather than using a 2 mm or more diameter needle, where positive bacteriology is obtained in over 90 % of biopsies [7]. They draw attention to the indications for surgery, as intractable pain, instability, and neurological changes, but make the point that minor neurology may resolve.…”
Section: Disc and Vertebral Body Infectionmentioning
confidence: 99%
“…To avoid pulmonary complications from posterolateral approach in thoracic, the transpedicular approach under fluoroscopic guidance gives best results. 13,14 The most common complications are pulmonary, neurologic, and infective disorders in these orders respectively. There were no such complications in our study.…”
Section: Discussionmentioning
confidence: 99%